The Effectiveness of Employee Performance of Ministry of Religious Affairs during Work from Home and The Factors that Influence It - Rosidah, Siti; Maarif, M. Syamsul; Sukmawati, Anggraini (Jurnal Manajemen, 2022)
Working from home as a new method of flexible work is being accelerated due to the Corona Virus Disease 2019 (COVID-19) pandemic. This new work system resulted in several changes that occurred in the workplace related to the work environment. Furthermore, changes occur in the use of higher technology. This indicates the importance of the availability of technology infrastructure while working from home. This study was conducted to analyze the effectiveness of employee performance while working from home. This study also aims to analyze the effect of work environment, technology infrastructure, work autonomy, and intrinsic motivation on employee performance. Data analysis was performed using Wilcoxon Signed Rank and Structural Equation Modeling Partial Least Square (SEM-PLS). The results show that employee performance is less effective when working from home. This is indicated by a decrease in employee performance. Work environment, technology infrastructure and intrinsic motivation have a significant effect on employee performance while working from home. Meanwhile, no significant effect was found between work autonomy and employee performance.